2017
DOI: 10.7717/peerj.3357
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacins: elucidation of their interactions with the cytoskeleton

Abstract: Cucurbitacins, a class of toxic tetracyclic triterpenoids in Cucurbitaceae, modulate many molecular targets. Here we investigated the interactions of cucurbitacin B, E and I with cytoskeletal proteins such as microtubule and actin filaments. The effects of cucurbitacin B, E and I on microtubules and actin filaments were studied in living cells (Hela and U2OS) and in vitro using GFP markers, immunofluorescence staining and in vitro tubulin polymerization assay. Cucurbitacin B, E and I apparently affected microt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…In recent years, many studies have reported that CuB can inhibit cell proliferation and induce apoptosis of different types of cancer cells, and it has become a potentially safe anticancer drug (Chen et al, 2012;Promkan, Dakeng, Chakrabarty, Bogler, & Patmasiriwat, 2013;Shukla et al, 2015;Zhang, Gao, & Yang, 2017). Previous studies have shown that CuB interacts with the cytoskeleton by affecting actin filaments and the microtubule, and the cytoskeleton appears to be an early target (Wang, Tanaka, Peixoto, & Wink, 2017;Zhang et al, 2014). However, the effect of CuB on the mechanical properties of breast cancer cells, which could influence the migration and invasion, has very rarely been reported.…”
mentioning
confidence: 99%
“…In recent years, many studies have reported that CuB can inhibit cell proliferation and induce apoptosis of different types of cancer cells, and it has become a potentially safe anticancer drug (Chen et al, 2012;Promkan, Dakeng, Chakrabarty, Bogler, & Patmasiriwat, 2013;Shukla et al, 2015;Zhang, Gao, & Yang, 2017). Previous studies have shown that CuB interacts with the cytoskeleton by affecting actin filaments and the microtubule, and the cytoskeleton appears to be an early target (Wang, Tanaka, Peixoto, & Wink, 2017;Zhang et al, 2014). However, the effect of CuB on the mechanical properties of breast cancer cells, which could influence the migration and invasion, has very rarely been reported.…”
mentioning
confidence: 99%
“…The cytotoxic effect of CuB was tested on HeLa and U2OS cells, and the IC 50 values were 12.2 and 17.07 μM, respectively. The inhibition of tubulin polymerization in vitro was observed with an IC 50 > 1 mM [13]. CuB from the leaves of Tunisian E. elaterium exhibited an anticancer effect and displayed anti-integrin activity in human glioblastoma U87 cells, with no cytotoxicity observed at concentrations up to 500 nM.…”
Section: Cucurbitacin B (1′)mentioning
confidence: 93%
“…The cytotoxic effect of CuE was tested on HeLa and U2OS cells, and the IC 50 values were 6.43 and 15.07 nM, respectively. The inhibition of tubulin polymerization in vitro had an IC 50 of 566.91 nM [13].…”
Section: Cucurbitacin E (4′)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that CuE could significantly inhibit the growth of breast cancer cells and HL-60 cells by inducing G2/M cell cycle arrest 14,22,23. Moreover, CuE could induce cell cycle arrest at the G2/M phase by altering mitotic spindles in U2OS, MCF7 and HeLa cancer cells 24. According to the current study, accumulation of CuE in GBM8401 and U-87-MG cells is the major cause leading to both the inhibition of cell proliferation and G2/M phase arrest.…”
mentioning
confidence: 97%